Carbon nanotube gel, gel electrolyte and preparation method and application thereof
By modifying carbon nanotubes with saturated hydrocarbyl imidazole ionic liquids and preparing carbon nanotube gels, the problem in the existing technology that carbon tube gels cannot achieve conductivity, flame retardancy and photohydrothermal evaporation capabilities at the same time is solved. Efficient photothermal conversion and seawater desalination performance.
Patent Information
- Application Number
- CN202411541679.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-17
AI Technical Summary
Existing carbon tube gels cannot achieve good conductivity, flame retardancy and photohydrothermal evaporation capabilities at the same time.
Carbon nanotube gels are prepared by surface modification of carbon nanotubes using imidazole ionic liquids containing saturated hydrocarbon groups to form a core-shell structure, and initiating polymerization through cobalt source irradiation or cross-linking agents.
The conductivity, flame retardancy and photohydrothermal evaporation ability of the carbon nanotube gel have been improved. It has excellent photothermal conversion efficiency and salt crystallization resistance, and is suitable for applications such as seawater desalination.
Smart Images

Figure CN119318921A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of carbon nanomaterial preparation, and in particular to a carbon nanotube gel, a gel electrolyte, and a preparation method and application thereof. Background Art
[0002] As a new type of carbon nanomaterial, carbon tube gel is widely used in electrochemical energy storage, sensor preparation and other fields due to its excellent electrical conductivity and mechanical properties. Ye Tiannan et al. combined irradiation grafting and irradiation crosslinking technology to prepare uniform carbon nanotube composite hydrogel by irradiation two-step method (Preparation and Properties of Carbon Nanotube / Polyacrylamide Composite Hydrogel [J]. Nuclear Technology, 2016, 39(02): 23-30.). In this study, acrylic acid groups were grafted onto the walls of carbon nanotubes to obtain modified carbon nanotubes, which effectively improved the dispersibility of carbon nanotubes in water. Then, the modified carbon nanotubes were crosslinked with acrylamide by irradiation to obtain uniform carbon nanotube composite hydrogel. However, the carbon nanotube composite hydrogel cannot achieve good electrical conductivity, flame retardancy, and photothermal evaporation ability at the same time.
[0003] The above problems can be solved well by using ionic liquids to modify the surface of carbon nanotubes. Ionic liquids are salts with anions and cations. As solvents, ionic liquids provide a new chemical environment for carbon nanotubes, overcoming their shortcomings of being easily aggregated into bundles and having poor dispersion in water and most organic solvents; as surface modifiers, ionic liquids can achieve surface functionalization of carbon nanotubes, giving carbon nanocomposites more excellent performance. However, according to research reports, ionic liquids suitable for radiation grafting technology are mostly two major types of ionic liquids whose cations contain acryloyl or vinyl unsaturated groups. Under irradiation, unsaturated hydrocarbons are easy to react because the double or triple bond structures in their molecules are easily affected by radiation and break or react with free radicals generated by radiation; in contrast, saturated hydrocarbon carbon atoms are connected by single bonds, and it is more difficult to form a stable molecular structure reaction. For ionic liquids whose cations are all saturated groups, carbon nanotubes can generally only be modified by mechanical blending, which has the disadvantages of easy detachment and difficult adhesion.
[0004] Therefore, providing a carbon nanotube gel suitable for irradiation-modified carbon nanotubes of ionic liquids in which all cations are saturated groups has important scientific significance and practical value. Summary of the invention
[0005] The technical problem to be solved by the present invention is to overcome the defect that carbon tube gel in the prior art cannot simultaneously achieve good electrical conductivity, flame retardancy, and light, water, and thermal evaporation capabilities, and provide a carbon nanotube gel, a gel electrolyte, and a preparation method and application thereof. The carbon nanotube gel provided by the present invention simultaneously has good electrical conductivity, flame retardancy, and light, water, and thermal evaporation capabilities.
[0006] The present invention solves the above technical problems through the following technical solutions.
[0007] The present invention provides a carbon nanotube gel, which comprises carbon nanotubes, gel, ionic liquid and water;
[0008] Wherein, the mass ratio of the carbon nanotubes to the gel is 1:(1-13); the mass ratio of the carbon nanotubes to the ionic liquid is 1:(1-13); and the mass ratio of the carbon nanotubes to the water is 1:(9-100).
[0009] In the present invention, preferably, the ionic liquid (through non-covalent bonds and / or covalent bonds) and the carbon nanotubes exist in the form of ionic liquid-modified carbon nanotubes; more preferably, part or all of the ionic liquid is grafted onto the carbon nanotubes through covalent bonds (i.e., grafting modification).
[0010] The non-covalent bond is, for example, a π-π interaction non-covalent bond.
[0011] In one embodiment of the present invention, the (partial or complete) ionic liquid covers the carbon nanotubes to form a core-shell structure (ie, the carbon nanotubes are the core and the ionic liquid is the shell).
[0012] In a certain embodiment of the present invention, the carbon nanotube gel is composed of the carbon nanotubes, the gel, the ionic liquid and water.
[0013] In the present invention, the mass ratio of the carbon nanotubes to the gel is, for example, (1:5.67) or (1:10).
[0014] In the present invention, preferably, the mass ratio of the carbon nanotubes to the ionic liquid is 1:(1-8), for example, (1:1), (1:1.67), (1:2), (1:3), (1:3.33), (1:4), (1:5) or (1:6.67).
[0015] In the present invention, the mass ratio of the carbon nanotubes to the water is, for example, (1:13.33) or (1:90).
[0016] In the present invention, preferably, the carbon nanotubes are selected from one or more of multi-walled carbon nanotubes, single-walled carbon nanotubes and double-walled carbon nanotubes.
[0017] In the present invention, preferably, the ionic liquid is an imidazole ionic liquid containing a saturated hydrocarbon group.
[0018] Among them, preferably, in the imidazolium ionic liquid containing a saturated hydrocarbon group, the imidazolium cation group containing a saturated hydrocarbon group is selected from one or more of 1-butyl-3-methylimidazolium cation, 1-octylimidazolium cation, 1-decylimidazolium cation and 1-hexylimidazolium cation.
[0019] Preferably, the anion of the imidazole ionic liquid containing a saturated hydrocarbon group is selected from one or more of chloride ion, borate ion, acetate ion and hexafluorophosphate ion.
[0020] Preferably, the imidazolium ionic liquid containing a saturated hydrocarbon group is selected from 1-butyl-3-methylimidazolium chloride ([BMIM]Cl), 1-butyl-3-methylimidazolium tetrafluoroborate ([BMIM][BF4]), 1-butyl-3-methylimidazolium hexafluorophosphate ([BMIM][PF6]), 1-octyl imidazolium chloride ([C8IM]Cl), 1-octyl imidazolium tetrafluoroborate ([C8IM]BF4), 1-decyl imidazolium chloride ([ The invention further comprises one or more of 1-hexylimidazole acetate ([C6Im]Ac), 1-butyl-3-methylimidazolium chloride ([BMIM]Cl), 1-octylimidazole tetrafluoroborate ([C8IM]BF4) and 1-decylimidazole tetrafluoroborate ([C10IM]BF4).
[0021] In the present invention, preferably, the gel is a polymer (gel) obtained by polymerizing an propylene monomer and / or a vinyl monomer.
[0022] Preferably, the acrylic monomer is selected from one or more of acrylamide, acrylic acid, methacrylic acid, methyl methacrylate and N-isopropylacrylamide.
[0023] The vinyl monomer is, for example, vinyl alcohol.
[0024] The present invention also provides a method for preparing carbon nanotube gel, which is prepared by the following method 1 or method 2:
[0025] Method 1: Mixture A is irradiated with a cobalt source or with a crosslinker and an initiator (for polymerization reaction) to obtain a carbon nanotube gel; wherein mixture A comprises carbon nanotubes, polymer monomers, ionic liquids and water; and the polymer monomers are propylene monomers and / or vinyl monomers;
[0026] Wherein, the mass ratio of the carbon nanotube to the polymer monomer is 1:(1-13); the mass ratio of the carbon nanotube to the ionic liquid is 1:(1-13); the mass ratio of the carbon nanotube to the water is 1:(9-18);
[0027] Method 2: Step 1, irradiating mixture B with a cobalt source to obtain mixture C; wherein mixture B comprises carbon nanotubes, ionic liquid and water; the mass ratio of the carbon nanotubes, the ionic liquid and the water is 1: (1-20): (1800-2200);
[0028] Step 2, irradiating the mixture D with a cobalt source or with a crosslinker and an initiator (for polymerization reaction) to obtain a carbon nanotube gel; wherein the mixture D comprises the mixture C, a polymer monomer and water; the polymer monomer is an propylene monomer and / or a vinyl monomer; the mass ratio of the mixture C, the polymer monomer and the water is (1-5): (3-35): (80-120);
[0029] The carbon nanotubes, propylene monomers, vinyl monomers, and ionic liquids are defined as described in any of the embodiments of the present application.
[0030] In a certain embodiment of the present invention, the raw materials are composed of the carbon nanotubes, the gel, the ionic liquid and water.
[0031] In the first or second aspect of the present invention, preferably, the carbon nanotubes are selected from one or more of multi-walled carbon nanotubes, single-walled carbon nanotubes and double-walled carbon nanotubes.
[0032] In the first or second embodiment of the present invention, preferably, the acrylic monomer is selected from one or more of acrylamide, acrylic acid, methacrylic acid, methyl methacrylate and N-isopropylacrylamide.
[0033] In the first or second aspect of the present invention, the vinyl monomer is, for example, vinyl alcohol.
[0034] In the first or second aspect of the present invention, preferably, the ionic liquid is an imidazole ionic liquid containing a saturated hydrocarbon group.
[0035] Among them, preferably, the imidazolium cation group containing a saturated hydrocarbon group in the imidazolium ionic liquid containing a saturated hydrocarbon group is selected from one or more of 1-butyl-3-methylimidazolium cation, 1-octylimidazolium cation, 1-decylimidazolium cation and 1-hexylimidazolium cation.
[0036] Preferably, the anion of the imidazole ionic liquid containing a saturated hydrocarbon group is selected from one or more of chloride ion, borate ion, acetate ion and hexafluorophosphate ion.
[0037] Preferably, the imidazolium ionic liquid containing a saturated hydrocarbon group is selected from 1-butyl-3-methylimidazolium chloride ([BMIM]Cl), 1-butyl-3-methylimidazolium tetrafluoroborate ([BMIM][BF4]), 1-butyl-3-methylimidazolium hexafluorophosphate ([BMIM][PF6]), 1-octyl imidazolium chloride ([C8IM]Cl), 1-octyl imidazolium tetrafluoroborate ([C8IM]BF4), 1-decyl imidazolium chloride ([ The invention further comprises one or more of 1-hexylimidazole acetate ([C6Im]Ac), 1-butyl-3-methylimidazolium chloride ([BMIM]Cl), 1-octylimidazole tetrafluoroborate ([C8IM]BF4) and 1-decylimidazole tetrafluoroborate ([C10IM]BF4).
[0038] In the first or second aspect of the present invention, the cobalt source is, for example, cobalt-60 gamma rays.
[0039] In the first or second embodiment of the present invention, the cross-linking agent may be a conventional cross-linking agent in the art, such as N,N'-methylenebisacrylamide (MBAA).
[0040] In the first embodiment of the present invention, preferably, the amount of the cross-linking agent used is 1%-3% by mass of the mixture A, for example, 1.4%.
[0041] In the second embodiment of the present invention, preferably, the amount of the cross-linking agent used accounts for 1%-3% by mass of the mixture D.
[0042] In the first or second embodiment of the present invention, the initiator may be a conventional initiator in the art, such as potassium persulfate (KPS).
[0043] In the first embodiment of the present invention, preferably, the amount of the initiator used is 1%-3% by mass of the mixture A, for example, 1.4%.
[0044] In the second embodiment of the present invention, preferably, the amount of the initiator used accounts for 1%-3% by mass of the mixture D.
[0045] In the first embodiment of the present invention, preferably, the mass ratio of the carbon nanotubes, the polymer monomers, the ionic liquid and the water is 1:(4-7):(1-8):(10-15), for example (0.3:1.7:0.5:4), (0.3:1.7:1:4) or (0.3:1.7:2:4).
[0046] In the first embodiment of the present invention, preferably, the absorbed dose of the cobalt source during irradiation is 5-200 kGy, for example, 5 kGy, 25 kGy or 50 kGy.
[0047] In the first mode of the present invention, preferably, before the cobalt source is irradiated, the mixture A is stirred evenly, and then nitrogen is introduced into the mixture A and sealed. The purpose of introducing nitrogen is to exclude air for protection.
[0048] Preferably, the stirring time is 1-3 hours.
[0049] Preferably, the nitrogen is introduced for 0.5-1 hour.
[0050] In the second embodiment of the present invention, preferably, in the mixture B, the mass ratio of the carbon nanotubes, the ionic liquid and the water is 1:(1-10):2000, for example, 1:1:2000, 1:2:2000, 1:3:2000, 1:4:2000 or 1:5:2000.
[0051] In the second embodiment of the present invention, preferably, in the mixture D, the mass ratio of the mixture C, the polymer monomer and the water is (1-5): (5-15): (80-120), for example, (1.5:10:90), (2:10:90), (2.5:10:90), (3:10:90) or (3.5:10:90).
[0052] In the second embodiment of the present invention, in the mixture D, the polymer monomer and the water exist in the form of an aqueous solution of the polymer monomer. Preferably, the mass concentration of the aqueous solution of the polymer monomer is 3%-35%, for example, 10%.
[0053] The aqueous solution of the polymer monomer is, for example, an aqueous solution of acrylic acid with a mass concentration of 10%.
[0054] In the second embodiment of the present invention, preferably, the absorbed dose of the cobalt source when irradiating the mixture B is 2-100 kGy, for example, 50 kGy.
[0055] In the second embodiment of the present invention, preferably, before irradiating the cobalt source, the mixture B is stirred evenly, and then the mixture B is sealed and nitrogen is introduced.
[0056] Preferably, the stirring time is 2-8 hours.
[0057] Preferably, the time for introducing nitrogen is 5 minutes to 1 hour.
[0058] In the second embodiment of the present invention, preferably, the absorbed dose of the cobalt source when irradiating the mixture D is 5-100 kGy, for example, 50 kGy.
[0059] In the second embodiment of the present invention, preferably, before the cobalt source is irradiated, the mixture D is stirred evenly, and then the mixture D is sealed and nitrogen is introduced.
[0060] Preferably, the stirring time is 2-8 hours.
[0061] Preferably, the time for introducing nitrogen is 5 minutes to 1 hour.
[0062] In a specific embodiment of the present invention, the preparation method of the carbon nanotube gel is selected from one of the following schemes:
[0063] Solution 1:
[0064] A cobalt source is used to irradiate a mixture A; wherein the mixture A comprises carbon nanotubes, polymer monomers, ionic liquids and water; wherein the carbon nanotubes are multi-walled carbon nanotubes; the polymer monomers are acrylamide and acrylic acid, and the mass ratio of acrylamide to acrylic acid is 1:0.7; the ionic liquid is 1-butyl-3-methylimidazole chloride; the mass ratio of the carbon nanotubes to the polymer monomers is 0.3:1.7; the mass ratio of the carbon nanotubes to the ionic liquids is 0.3:1; the mass ratio of the carbon nanotubes to the water is 0.3:4; and the absorbed dose during irradiation with the cobalt source is 50 kGy;
[0065] Option 2:
[0066] A cobalt source irradiates a mixture A; wherein the mixture A comprises carbon nanotubes, polymer monomers, ionic liquids and water; wherein the carbon nanotubes are multi-walled carbon nanotubes; the polymer monomers are acrylamide and acrylic acid, and the mass ratio of acrylamide to acrylic acid is 1:0.7; the ionic liquid is 1-butyl-3-methylimidazole chloride; the mass ratio of the carbon nanotubes to the polymer monomers is 0.3:1.7; the mass ratio of the carbon nanotubes to the ionic liquids is 0.3:2; the mass ratio of the carbon nanotubes to the water is 0.3:4; the absorbed dose during the irradiation of the cobalt source is 50 kGy;
[0067] Option 3:
[0068] A cobalt source irradiates a mixture A; wherein the mixture A comprises carbon nanotubes, polymer monomers, ionic liquids and water; wherein the carbon nanotubes are multi-walled carbon nanotubes; the polymer monomers are acrylamide and acrylic acid, and the mass ratio of acrylamide to acrylic acid is 1:0.7; the ionic liquid is 1-butyl-3-methylimidazole chloride; the mass ratio of the carbon nanotubes to the polymer monomers is 0.3:1.7; the mass ratio of the carbon nanotubes to the ionic liquids is 0.3:0.5; the mass ratio of the carbon nanotubes to the water is 0.3:4; the absorbed dose during the irradiation of the cobalt source is 50 kGy;
[0069] Option 4:
[0070] A cobalt source is used to irradiate a mixture A; wherein the mixture A comprises carbon nanotubes, polymer monomers, ionic liquids and water; wherein the carbon nanotubes are multi-walled carbon nanotubes; the polymer monomers are acrylamide and acrylic acid, and the mass ratio of acrylamide to acrylic acid is 1:0.7; the ionic liquid is 1-butyl-3-methylimidazole chloride; the mass ratio of the carbon nanotubes to the polymer monomers is 0.3:1.7; the mass ratio of the carbon nanotubes to the ionic liquids is 0.3:1; the mass ratio of the carbon nanotubes to the water is 0.3:4; and the absorbed dose during irradiation with the cobalt source is 25 kGy;
[0071] Option 5:
[0072] A cobalt source is used to irradiate a mixture A; wherein the mixture A comprises carbon nanotubes, polymer monomers, ionic liquids and water; wherein the carbon nanotubes are multi-walled carbon nanotubes; the polymer monomers are acrylamide and acrylic acid, and the mass ratio of acrylamide to acrylic acid is 1:0.7; the ionic liquid is 1-butyl-3-methylimidazole chloride; the mass ratio of the carbon nanotubes to the polymer monomers is 0.3:1.7; the mass ratio of the carbon nanotubes to the ionic liquids is 0.3:1; the mass ratio of the carbon nanotubes to the water is 0.3:4; and the absorbed dose during irradiation with the cobalt source is 5 kGy;
[0073] Option 6:
[0074] A cobalt source is used to irradiate a mixture A; wherein the mixture A comprises carbon nanotubes, polymer monomers, ionic liquids and water; wherein the carbon nanotubes are single-walled carbon nanotubes; the polymer monomers are acrylamide and acrylic acid, and the mass ratio of acrylamide to acrylic acid is 1:0.7; the ionic liquid is 1-butyl-3-methylimidazole chloride; the mass ratio of the carbon nanotubes to the polymer monomers is 0.3:1.7; the mass ratio of the carbon nanotubes to the ionic liquids is 0.3:1; the mass ratio of the carbon nanotubes to the water is 0.3:4; and the absorbed dose during irradiation with the cobalt source is 50 kGy;
[0075] Option 7:
[0076] A cobalt source is used to irradiate mixture B to obtain mixture C; wherein mixture B comprises carbon nanotubes, ionic liquids and water; wherein the carbon nanotubes are single-walled carbon nanotubes; the ionic liquids are 1-butyl-3-methylimidazolium chloride; the mass ratio of the carbon nanotubes, the ionic liquids and the water is 1:1:2000; and the absorbed dose of the cobalt source when irradiating mixture B is 50 kGy;
[0077] Then, a cobalt source is used to irradiate the mixture D; wherein the mixture D comprises the mixture C, a polymer monomer and water; the polymer monomer is acrylic acid; the mass ratio of the mixture C, the polymer monomer and the water is (1.5:10:90); the absorbed dose when the cobalt source irradiates the mixture D is 50 kGy;
[0078] Option 8:
[0079] A cobalt source is used to irradiate mixture B to obtain mixture C; wherein mixture B comprises carbon nanotubes, ionic liquids and water; wherein the carbon nanotubes are single-walled carbon nanotubes; the ionic liquids are 1-butyl-3-methylimidazolium chloride; the mass ratio of the carbon nanotubes, the ionic liquids and the water is 1:2:2000; and the absorbed dose of the cobalt source when irradiating mixture B is 50 kGy;
[0080] Then, a cobalt source is used to irradiate the mixture D; wherein the mixture D comprises the mixture C, a polymer monomer and water; the polymer monomer is acrylic acid; the mass ratio of the mixture C, the polymer monomer and the water is (2:10:90); the absorbed dose when the cobalt source irradiates the mixture D is 50 kGy;
[0081] Option Nine:
[0082] A cobalt source is used to irradiate mixture B to obtain mixture C; wherein mixture B comprises carbon nanotubes, ionic liquids and water; wherein the carbon nanotubes are single-walled carbon nanotubes; the ionic liquids are 1-butyl-3-methylimidazolium chloride; the mass ratio of the carbon nanotubes, the ionic liquids and the water is 1:3:2000; and the absorbed dose of the cobalt source when irradiating mixture B is 50 kGy;
[0083] Then, a cobalt source is used to irradiate the mixture D; wherein the mixture D comprises the mixture C, a polymer monomer and water; the polymer monomer is acrylic acid; the mass ratio of the mixture C, the polymer monomer and the water is (2.5:10:90); the absorbed dose when the cobalt source irradiates the mixture D is 50 kGy;
[0084] Option 10:
[0085] A cobalt source is used to irradiate mixture B to obtain mixture C; wherein mixture B comprises carbon nanotubes, ionic liquids and water; wherein the carbon nanotubes are single-walled carbon nanotubes; the ionic liquids are 1-butyl-3-methylimidazolium chloride; the mass ratio of the carbon nanotubes, the ionic liquids and the water is 1:4:2000; and the absorbed dose of the cobalt source when irradiating mixture B is 50 kGy;
[0086] Then, a cobalt source is used to irradiate the mixture D; wherein the mixture D comprises the mixture C, a polymer monomer and water; the polymer monomer is acrylic acid; the mass ratio of the mixture C, the polymer monomer and the water is (3:10:90); the absorbed dose when the cobalt source irradiates the mixture D is 50 kGy;
[0087] Plan 11:
[0088] A cobalt source is used to irradiate mixture B to obtain mixture C; wherein mixture B comprises carbon nanotubes, ionic liquids and water; wherein the carbon nanotubes are single-walled carbon nanotubes; the ionic liquids are 1-butyl-3-methylimidazolium chloride; the mass ratio of the carbon nanotubes, the ionic liquids and the water is 1:5:2000; and the absorbed dose when the cobalt source is used to irradiate mixture B is 50 kGy;
[0089] Then, a cobalt source is used to irradiate the mixture D; wherein the mixture D comprises the mixture C, a polymer monomer and water; the polymer monomer is acrylic acid; the mass ratio of the mixture C, the polymer monomer and the water is (3.5:10:90); the absorbed dose when the cobalt source irradiates the mixture D is 50 kGy;
[0090] Plan 12:
[0091] The mixture A is polymerized by a crosslinking agent and an initiator to obtain a carbon nanotube gel; wherein the mixture A includes carbon nanotubes, polymer monomers, ionic liquids and water; wherein the carbon nanotubes are multi-walled carbon nanotubes; the polymer monomers are acrylamide and acrylic acid; the crosslinking agent is N,N'-methylenebisacrylamide; the initiator is potassium persulfate, and the mass ratio of acrylamide to the acrylic acid is 1:0.7; the ionic liquid is 1-butyl-3-methylimidazole chloride; the mass ratio of the carbon nanotubes to the polymer monomers is 0.3:1.7; the mass ratio of the carbon nanotubes to the ionic liquids is 0.3:1; the mass ratio of the carbon nanotubes to the water is 0.3:4; the mass ratio of the crosslinking agent to the total mass of the mixture A, the crosslinking agent and the initiator is 0.1:7.2; the mass ratio of the initiator to the total mass of the mixture A, the crosslinking agent and the initiator is 0.1:7.2.
[0092] The present invention also provides a carbon nanotube gel prepared by the above-mentioned method for preparing the carbon nanotube gel.
[0093] The present invention also provides a gel electrolyte, which is obtained by subjecting the carbon nanotube gel and an aqueous solution of alkali to adsorption and swelling equilibrium.
[0094] In the present invention, preferably, the alkali is selected from one or more of potassium hydroxide, calcium hydroxide and sodium hydroxide.
[0095] In the present invention, preferably, the mass percentage of the alkali in the aqueous solution of the alkali is 5%-60%, for example 30%.
[0096] In some preferred embodiments of the present invention, the gel electrolyte is obtained by allowing the carbon nanotube gel to stand in the alkaline aqueous solution for 1-5 hours and then absorbing surface moisture.
[0097] The present invention also provides a use of the carbon nanotube gel as described above as a gel material in the preparation of gel electrolyte and / or seawater desalination.
[0098] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0099] The reagents and raw materials used in the present invention are commercially available.
[0100] The positive and progressive effects of the present invention are:
[0101] The carbon nanotube gel provided by the present invention has good electrical conductivity, flame retardancy, and light-water-heat evaporation capacity. The carbon nanotube gel provided by the present invention has excellent light-heat conversion efficiency and salt crystallization resistance. It can not only efficiently absorb solar energy and convert it into heat energy, thereby accelerating the evaporation of seawater, but also maintain its performance stability for a long time, providing a green and efficient solution for seawater desalination.
[0102] The preparation method of the carbon nanotube gel provided by the present invention is simple, environmentally friendly, does not require organic solvents or toxic reagents, is pollution-free and safe. In addition, it is applicable to a variety of ionic liquids and carbon tube types and has good adjustability and versatility.
[0103] The carbon nanotube gel provided by the present invention has the following effects when applied to gel electrolyte: (1) It has good mechanical strength and stability, which can effectively prevent the leakage of electrolyte and the damage of the internal structure of the battery, and improve the overall safety and durability of the battery. (2) It is non-flammable and non-explosive, and has higher safety than traditional liquid electrolytes. It is particularly suitable for application fields with high safety requirements, such as portable electronic devices and electric vehicles. (3) It has a certain flexibility and can adapt to changes in battery shape and the influence of external stress, which helps to maintain the structural integrity and performance stability of the battery. (4) It can form a good contact interface between the electrode and the electrolyte, reduce the interface impedance, and thus improve the energy density and power density of the battery. (5) By adjusting the composition and structure of the gel electrolyte, the battery performance can be optimized and customized to meet the specific needs of different application fields. (6) It has excellent light and water evaporation performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0104] Figure 1 This is a physical picture of the carbon nanotube gel prepared in Example 1.
[0105] Figure 2 This is a scanning electron microscope image of the carbon nanotube gel prepared in Example 1.
[0106] Figure 3 This is the XRD spectrum of the carbon nanotube gel prepared in Example 1.
[0107] Figure 4 This is the XPS spectrum of the carbon nanotube gel prepared in Example 1.
[0108] Figure 5 This is a photograph of the gel electrolyte obtained in Example 7.
[0109] Figure 6 This is a state diagram of the carbon nanotube gel obtained in Example 10 at various stages in the preparation process.
[0110] Figure 7 This is the thermogravimetric analysis diagram of the carbon nanotube gel obtained in Example 14.
[0111] Figure 8 This is a photo of the product obtained in Comparative Example 1.
[0112] Fig. 9 This is a photo of the product obtained in Comparative Example 2.
[0113] Fig.10 This is a bar graph of the photothermal evaporation rate of the carbon nanotube gels prepared in Examples 10-14. DETAILED DESCRIPTION
[0114] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0115] The reagents or instruments used are not marked with the manufacturer, and are all conventional products that can be purchased through regular channels. The raw materials and instrument information involved in the examples and comparative examples of the present invention are shown in Table 1:
[0116] Table 1
[0117]
[0118] Example 1
[0119] This embodiment provides a carbon nanotube gel, and the preparation method thereof is as follows:
[0120] S1, weigh 0.3 g of multi-walled carbon nanotubes into a beaker, and add 4 ml of water;
[0121] S2, adding 1 g of acrylamide and 0.7 g of acrylic acid to the mixture obtained in S1;
[0122] S3, adding 1 gram of ionic liquid 1-butyl-3-methylimidazolium chloride to the mixture obtained in S2;
[0123] S4, fully stirring the mixture obtained in S3 for 2 hours;
[0124] S5, sealing the mixture obtained in S4 and introducing nitrogen for 5 minutes;
[0125] S6. Irradiate the sample obtained in S5 with a cobalt source with an absorbed dose of 50 kGy to obtain a carbon nanotube gel.
[0126] Example 2
[0127] This embodiment provides a carbon nanotube gel, which is different from the embodiment 1 only in that the mass of the ionic liquid in step S3 is 2 g, and the other operations and conditions are the same as those in the embodiment 1.
[0128] Example 3
[0129] This embodiment provides a carbon nanotube gel, which is different from the embodiment 1 only in that the mass of the ionic liquid in step S3 is 0.5 g, and the other operations and conditions are the same as those in the embodiment 1.
[0130] Example 4
[0131] This embodiment provides a carbon nanotube gel, which is different from the embodiment 1 only in that the absorbed dose in step S6 is 25 kGy, and the other operations and conditions are the same as those in the embodiment 1.
[0132] Example 5
[0133] This embodiment provides a carbon nanotube gel, which is different from the embodiment 1 only in that the absorbed dose in step S6 is 5 kGy, and the other operations and conditions are the same as those in the embodiment 1.
[0134] Example 6
[0135] This embodiment provides a gel electrolyte, and the preparation method thereof is as follows:
[0136] S1. Take the carbon nanotube gel prepared in Example 2 and cut it into a size of 1.5 cm*1.5 cm*0.3 cm (length; width; height);
[0137] S2, weigh 7.5g of potassium hydroxide into a beaker, add 17.5g of water thereto, mix well, and obtain a potassium hydroxide aqueous solution with a mass fraction of 30%;
[0138] S3, placing the carbon nanotube gel cut in S1 into the solution obtained in S2, and leaving it to stand for 2 hours to obtain a gel electrolyte with water;
[0139] S4. Take out the gel electrolyte with water obtained in S3 and remove the surface water with dry cotton cloth to obtain a gel electrolyte.
[0140] Example 7
[0141] This embodiment provides a gel electrolyte, which is different from Embodiment 1 only in that step S2 is "weighing 10 g of potassium hydroxide into a beaker, adding 15 g of water thereto, mixing evenly, to obtain a potassium hydroxide aqueous solution with a mass fraction of 40%", and the remaining operations and conditions are the same as those of Embodiment 6.
[0142] Example 8
[0143] This embodiment provides a gel electrolyte, which differs from Embodiment 1 only in that step S2 is "weighing 12.5 g of potassium hydroxide into a beaker, adding 12.5 g of water thereto, mixing evenly, to obtain a potassium hydroxide aqueous solution with a mass fraction of 50%", and the remaining operations and conditions are the same as those of Embodiment 6.
[0144] Example 9
[0145] This embodiment provides a gel electrolyte, which is different from Embodiment 1 only in that step S2 is "weighing 10 g of sodium hydroxide into a beaker, adding 15 g of water thereto, mixing evenly, to obtain a sodium hydroxide aqueous solution with a mass fraction of 40%", and the remaining operations and conditions are the same as those of Embodiment 6.
[0146] Example 10
[0147] This embodiment provides a carbon nanotube gel, and the preparation method thereof is as follows:
[0148] S1, weigh 0.1 g of multi-walled carbon nanotubes into a beaker, and add 200 ml of water thereto;
[0149] S2, adding 0.1 g of ionic liquid 1-butyl-3-methylimidazolium chloride to the mixture obtained in S1;
[0150] S3, the mixture obtained in S2 was fully stirred for 1 h, sealed and introduced with nitrogen;
[0151] S4, irradiating the sample obtained in S3 with a cobalt source, with an absorbed dose of 50 kGy;
[0152] S5, filtering and drying the sample obtained in S4 to obtain a solid powder;
[0153] S6, mixing the solid powder obtained in S5 with 10 g of an acrylic acid aqueous solution having a mass concentration of 10%;
[0154] S7, fully stirring the mixture obtained in S6;
[0155] S8, sealing the mixture obtained in S7 and introducing nitrogen;
[0156] S9. Irradiate the sample obtained in S8 with a cobalt source with an absorbed dose of 50 kGy to obtain a gel electrolyte.
[0157] Embodiment 11
[0158] This embodiment provides a carbon nanotube gel, which is different from Embodiment 11 only in that the mass of the ionic liquid in step S2 is 0.2 g, and the rest of the operations and conditions are the same as those in Embodiment 10.
[0159] Example 12
[0160] This embodiment provides a carbon nanotube gel, which is different from Embodiment 11 only in that the mass of the ionic liquid in step S2 is 0.3 g, and the other operations and conditions are the same as those of Embodiment 10.
[0161] Embodiment 13
[0162] This embodiment provides a carbon nanotube gel, which is different from Embodiment 11 only in that the mass of the ionic liquid in step S2 is 0.4 g, and the other operations and conditions are the same as those of Embodiment 10.
[0163] Embodiment 14
[0164] This embodiment provides a carbon nanotube gel, which is different from Embodiment 11 only in that the mass of the ionic liquid in step S2 is 0.5 g, and the other operations and conditions are the same as those of Embodiment 10.
[0165] Embodiment 15
[0166] This embodiment provides a carbon nanotube gel, which is different from the embodiment 1 only in that the "multi-walled carbon nanotube" is replaced by "single-walled carbon nanotube" in step S1, and the rest of the operations and conditions are the same as those in the embodiment 1.
[0167] Example 16
[0168] This embodiment provides a carbon nanotube gel, and the preparation method thereof is as follows:
[0169] S1, take 0.3 g of multi-walled carbon nanotubes in a beaker and add 4 ml of water;
[0170] S2, adding 1 g of acrylamide and 0.7 g of acrylic acid to the mixture obtained in S1;
[0171] S3, adding 1 gram of ionic liquid 1-butyl-3-methylimidazolium chloride to the mixture obtained in S2;
[0172] S4. Add 0.1 g of cross-linking agent N,N'-methylenebisacrylamide (MBAA) to the mixture obtained in S4 and stir until dissolved.
[0173] S5. Add 0.1 g of initiator potassium persulfate (KPS) to the mixture obtained in S5 and stir evenly.
[0174] S6. Let stand for 24 hours to obtain a uniform gel.
[0175] Comparative Example 1
[0176] Comparative Example 1 provides a carbon nanotube gel, which is different from Example 1 only in that the mass of the multi-walled carbon nanotubes in step S1 is 0.5 g, and the other operations and conditions are the same as those in Example 1.
[0177] Comparative Example 2
[0178] Comparative Example 2 provides a carbon nanotube gel, which is different from Example 1 only in that the mass of the multi-walled carbon nanotubes in step S1 is 0.2 g, and the other operations and conditions are the same as those in Example 1.
[0179] Comparative Example 3
[0180] Comparative Example 3 provides a carbon nanotube gel, which differs from Example 10 only in that the ionic liquid "1-butyl-3-methylimidazolium chloride" is replaced by "1-dodecylimidazolium chloride" in step S2, and the remaining operations and conditions are the same as those in Example 10.
[0181] Comparative Example 4
[0182] This comparative example provides a carbon nanotube gel, which differs from Example 1 only in that the ionic liquid "1-butyl-3-methylimidazolium chloride" is replaced by "1-vinyl-3-butylimidazolium chloride" in step S3, and the remaining operations and conditions are the same as those in Example 1.
[0183] Effect Example 1
[0184] The actual picture of the carbon nanotube gel prepared in Example 1 is as follows Figure 1 As shown in the scanning electron microscope image Figure 2 As shown, the detection conditions of the scanning electron microscope image are: voltage 15.00kV, magnification 500X.
[0185] The XRD spectrum of the carbon nanotube gel prepared in Example 1 is as follows Figure 3 As shown, the figure shows that the carbon nanotube gel prepared in Example 1 contains XRD characteristic peaks of carbon nanotubes, indicating that carbon nanotubes are present in the prepared material.
[0186] The XPS spectrum of the carbon nanotube gel prepared in Example 1 is as follows: Figure 4 As shown in this figure, the XPS N1s fine spectrum shows an additional peak at 401.7 eV, corresponding to the imidazolium cation (N + ), indicating that the carbon nanotube gel prepared in Example 1 contains ionic liquid.
[0187] The photo of the gel electrolyte obtained in Example 7 is as follows Figure 5 shown.
[0188] The state diagram of the carbon nanotube gel obtained in Example 10 at each stage of the preparation process is as follows Figure 6 As shown, Figure 6 a in the figure indicates that the ionic liquid and multi-walled carbon nanotubes are in a layered state at the beginning. After irradiation, Figure 6 As shown in b, multi-walled carbon nanotubes modified with ionic liquid are obtained, which are no longer stratified. After being irradiated and cross-linked with acrylic acid, Figure 6 As shown in c, the carbon nanotube gel of this embodiment is finally obtained.
[0189] Thermogravimetric analysis of the carbon nanotube gel obtained in Example 14 is shown in FIG. Figure 7As shown in the figure, the carbon nanotube gel prepared in Example 14 has obvious heat loss compared with pure multi-walled carbon nanotubes, and its trend is the same as that of the ionic liquid (1-butyl-3-methylimidazolium chloride), indicating that the carbon nanotube gel prepared in Example 14 is indeed loaded with ionic liquid.
[0190] The photo of the product obtained in Comparative Example 1 is as follows Figure 8 As shown in the figure, the product obtained in Comparative Example 1 presents an inhomogeneous structure, and there are carbon nanotubes at the top that are not coated by the polymer gel. Therefore, the quality of the multi-walled carbon nanotubes is too high, and a uniform carbon nanotube gel cannot be prepared.
[0191] The photo of the product obtained in Comparative Example 2 is as follows Fig. 9 As shown in the figure, it is shown that the carbon nanotubes are not uniformly dispersed in the polymer gel. Therefore, the quality of the multi-walled carbon nanotubes is too low. In step S4, they cannot be in the form of a slurry, and ultimately a uniform carbon nanotube gel cannot be prepared.
[0192] Since the chain length of the ionic liquid used in Comparative Example 3 is too long, in step S4, it is impossible to obtain Figure 6 The multi-walled carbon nanotubes modified with ionic liquid shown in b ultimately cannot produce carbon nanotube gel.
[0193] Effect Example 2
[0194] The following performance tests were performed on the carbon nanotube gels obtained in Examples 1-5, Examples 10-16, the gel electrolytes obtained in Examples 6-9, and the carbon nanotube gels obtained in Comparative Examples 1-3, respectively:
[0195] (1) Conductivity test method
[0196] The ionic conductivity was calculated from the AC impedance spectrum, which was measured on an electrochemical workstation (CHI 760D). The carbon nanotube gel or gel electrolyte was placed between two stainless steel plates of the same size and tested in the frequency range of 10kHz to 0.01Hz. The equation for calculating the ionic conductivity σ is: 𝜎=l / 𝑅𝐴;
[0197] Where σ is the ionic conductivity of the carbon nanotube gel or gel electrolyte, and l, 𝑅, and 𝐴 represent the thickness, volume resistance, and test area of the carbon nanotube gel or gel electrolyte, respectively.
[0198] (2) Open circuit voltage test method
[0199] Cut the zinc sheet (thickness 1mm) into 1.5cm*1.5cm (length; width) size; cut the nickel mesh loaded with cobalt tetroxide (thickness 5mm) into 1.5cm*1.5cm (length; width) size; assemble the battery in the order of zinc sheet-carbon nanotube gel or gel electrolyte-nickel mesh, and test the battery open circuit voltage.
[0200] (3) Test method for the evaporation capacity of solar water heater
[0201] The evaporation rate was determined by monitoring the change of evaporated water volume over time using a balance. Photothermal evaporation rate (Rvap) (kg·m -2 h -1 ) can be expressed by the equation: Rvap=Δm / (S*Δt). Δm is the mass of evaporated water, S is the illuminated surface area of carbon nanotube gel, and Δt is the evaporation time.
[0202] (4) Test method for peak heat release rate
[0203] At 35 kW / m 2 Cone calorimeter tests (CCT) were performed on a FTT cone calorimeter compliant with ISO 5660 at a heat flux of 100 mm × 100 mm × 3 mm (sample size: 100 mm × 100 mm × 3 mm).
[0204] The performance test structures of the carbon nanotube gels obtained in Examples 1-5 and Examples 10-16, the gel electrolytes obtained in Examples 6-9, and the carbon nanotube gels obtained in Comparative Examples 1-3 are shown in Table 2.
[0205] Table 2
[0206]
[0207] As shown in Table 2, the carbon nanotube gels prepared in Examples 1-5 and 10-16 of the present application have good electrical conductivity, flame retardancy, and photothermal evaporation capabilities. As shown in Comparative Examples 1 and 2, the carbon nanotube gels of the present application can only be prepared when the raw materials are in a specific ratio. As shown in Comparative Example 3, only specific ionic liquids can be used to prepare the carbon nanotube gels of the present application. The bar graph of the photothermal evaporation rate of the carbon nanotube gels prepared in Examples 10-14 is shown in Fig.10 As shown, it is shown that the amount of ionic liquid has a significant effect on the photothermal evaporation rate.
Claims
1. A carbon nanotube gel, characterized in that: It includes carbon nanotubes, gels, ionic liquids and water; Wherein, the mass ratio of the carbon nanotubes to the gel is 1:(1-13); the mass ratio of the carbon nanotubes to the ionic liquid is 1:(1-13); and the mass ratio of the carbon nanotubes to the water is 1:(9-100).
2. The carbon nanotube gel according to claim 1, characterized in that It meets one or more of the following conditions: (1) The ionic liquid covers the carbon nanotubes to form a core-shell structure; (2) The carbon nanotube gel is composed of the carbon nanotubes, the gel, the ionic liquid and water; (3) The mass ratio of the carbon nanotubes to the gel is (1:5.67) or (1:10); (4) The mass ratio of the carbon nanotubes to the ionic liquid is 1:(1-8), for example, (1:1), (1:1.67), (1:2), (1:3), (1:3.33), (1:4), (1:5) or (1:6.67); (5) The mass ratio of the carbon nanotubes to the water is, for example, (1: 13.33) or (1:90); (6) The carbon nanotubes are selected from one or more of multi-walled carbon nanotubes, single-walled carbon nanotubes and double-walled carbon nanotubes; (7) The ionic liquid is an imidazole ionic liquid containing a saturated hydrocarbon group; Preferably, in the imidazolium ionic liquid containing a saturated hydrocarbon group, the imidazolium cation group containing a saturated hydrocarbon group is selected from one or more of 1-butyl-3-methylimidazolium cation, 1-octylimidazolium cation, 1-decylimidazolium cation and 1-hexylimidazolium cation; Preferably, the anion of the imidazole ionic liquid containing a saturated hydrocarbon group is selected from one or more of chloride ions, borate ions, acetate ions and hexafluorophosphate ions; Wherein, preferably, the imidazole ionic liquid containing a saturated hydrocarbon group is selected from one or more of 1-butyl-3-methylimidazolium chloride, 1-butyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium hexafluorophosphate, 1-octylimidazole chloride, 1-octylimidazole tetrafluoroborate, 1-decylimidazolium chloride, 1-decylimidazolium tetrafluoroborate and 1-hexylimidazolium acetate, more preferably selected from one or more of 1-hexylimidazolium acetate, 1-butyl-3-methylimidazolium chloride, 1-octylimidazole tetrafluoroborate and 1-decylimidazolium tetrafluoroborate; (8) The gel is a polymer obtained by polymerization of acrylic monomers and / or vinyl monomers; Preferably, the acrylic monomer is selected from one or more of acrylamide, acrylic acid, methacrylic acid, methyl methacrylate and N-isopropylacrylamide; The vinyl monomer is, for example, vinyl alcohol.
3. A method for preparing carbon nanotube gel, characterized in that: It is prepared by the following method 1 or method 2: Method 1: irradiating mixture A with a cobalt source or with a crosslinker and an initiator to obtain a carbon nanotube gel; wherein mixture A comprises carbon nanotubes, polymer monomers, ionic liquids and water; and the polymer monomers are propylene monomers and / or vinyl monomers; Wherein, the mass ratio of the carbon nanotube to the polymer monomer is 1:(1-13); the mass ratio of the carbon nanotube to the ionic liquid is 1:(1-13); the mass ratio of the carbon nanotube to the water is 1:(9-18); Method 2: Step 1, irradiating mixture B with a cobalt source to obtain mixture C; wherein mixture B comprises carbon nanotubes, ionic liquid and water; the mass ratio of the carbon nanotubes, the ionic liquid and the water is 1: (1-20): (1800-2200); Step 2, irradiating the mixture D with a cobalt source or with a crosslinker and an initiator to obtain a carbon nanotube gel; wherein the mixture D comprises the mixture C, a polymer monomer and water; the polymer monomer is an propylene monomer and / or a vinyl monomer; the mass ratio of the mixture C, the polymer monomer and the water is (1-5): (3-35): (80-120); The carbon nanotubes, propylene monomers, vinyl monomers and ionic liquids are defined as described in claim 2.
4. The method for preparing the carbon nanotube gel according to claim 3, characterized in that: It meets one or more of the following conditions: (1) Its raw materials consist of the carbon nanotubes, the gel, the ionic liquid and water; (2) In method 1 or method 2, the carbon nanotubes are selected from one or more of multi-walled carbon nanotubes, single-walled carbon nanotubes and double-walled carbon nanotubes; (3) In the first or second method, the acrylic monomer is selected from one or more of acrylamide, acrylic acid, methacrylic acid, methyl methacrylate and N-isopropylacrylamide; (4) In method 1 or method 2, the vinyl monomer is vinyl alcohol; (5) In the first or second method, the ionic liquid is an imidazole ionic liquid containing a saturated hydrocarbon group; Preferably, the imidazolium cation group containing a saturated hydrocarbon group in the imidazolium ionic liquid containing a saturated hydrocarbon group is selected from one or more of 1-butyl-3-methylimidazolium cation, 1-octylimidazolium cation, 1-decylimidazolium cation and 1-hexylimidazolium cation; Preferably, the anion of the imidazole ionic liquid containing a saturated hydrocarbon group is selected from one or more of chloride ions, borate ions, acetate ions and hexafluorophosphate ions; Wherein, preferably, the imidazole ionic liquid containing a saturated hydrocarbon group is selected from one or more of 1-butyl-3-methylimidazolium chloride, 1-butyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium hexafluorophosphate, 1-octylimidazole chloride, 1-octylimidazole tetrafluoroborate, 1-decylimidazolium chloride, 1-decylimidazolium tetrafluoroborate and 1-hexylimidazolium acetate, more preferably selected from one or more of 1-hexylimidazolium acetate, 1-butyl-3-methylimidazolium chloride, 1-octylimidazole tetrafluoroborate and 1-decylimidazolium tetrafluoroborate; (6) In method 1 or method 2, the cobalt source is cobalt 60 gamma ray; (7) In method 1 or method 2, the cross-linking agent is N,N'-methylenebisacrylamide; (8) In the first embodiment, the amount of the cross-linking agent used is 1%-3% by weight of the mixture A, for example, 1.4%; (9) In the second method, the amount of the cross-linking agent used is 1%-3% by weight of the mixture D; (10) In method 1 or method 2, the initiator is potassium persulfate; (11) In the first embodiment, the amount of the initiator used is 1%-3% by weight of the mixture A, for example, 1.4% by weight; (12) In the second method, the amount of the initiator used is 1%-3% by weight of the mixture D.
5. The method for preparing the carbon nanotube gel according to claim 3, characterized in that: It meets one or more of the following conditions: (1) In method 1, the mass ratio of the carbon nanotubes, the polymer monomer, the ionic liquid and the water is 1:(4-7):(1-8):(10-15), for example (0.3:1.7:0.5:4), (0.3:1.7:1:4) or (0.3:1.7:2:4); (2) In the first method, the absorbed dose of the cobalt source during irradiation is 5-200 kGy, for example, 5 kGy, 25 kGy or 50 kGy; (3) In method 1, before the cobalt source is irradiated, the mixture A is stirred evenly, and then nitrogen is introduced into the mixture A and sealed; (4) In the second method, in the mixture B, the mass ratio of the carbon nanotubes, the ionic liquid and the water is 1:(1-10):2000, for example, 1:1:2000, 1:2:2000, 1:3:2000, 1:4:2000 or 1:5:2000; (5) In the second method, in the mixture D, the mass ratio of the mixture C, the polymer monomer and the water is (1-5): (5-15): (80-120), for example, (1.5:10:90), (2:10:90), (2.5:10:90), (3: 10:90) or (3.5:10:90); (6) In the second method, in the mixture D, the polymer monomer and the water exist in the form of an aqueous solution of the polymer monomer, and the mass concentration of the aqueous solution of the polymer monomer is 3%-35%, for example, 10%; The aqueous solution of the polymer monomer is, for example, an aqueous solution of acrylic acid with a mass concentration of 10%; (7) In the second method, the absorbed dose of the cobalt source when irradiating the mixture B is 2-100 kGy, for example, 50 kGy; (8) In the second method, before the cobalt source is irradiated, the mixture B is stirred evenly, and then the mixture B is sealed and nitrogen is introduced; (9) In the second method, the absorbed dose of the cobalt source when irradiating the mixture D is 5-100 kGy, for example, 50 kGy; (10) In the second method, before the cobalt source is irradiated, the mixture D is stirred evenly, and then the mixture D is sealed and nitrogen is introduced.
6. The method for preparing the carbon nanotube gel according to claim 3, characterized in that: The preparation method of the carbon nanotube gel is selected from one of the following schemes: Solution 1: A cobalt source is used to irradiate a mixture A; wherein the mixture A comprises carbon nanotubes, polymer monomers, ionic liquids and water; wherein the carbon nanotubes are multi-walled carbon nanotubes; the polymer monomers are acrylamide and acrylic acid, and the mass ratio of acrylamide to acrylic acid is 1:0.7; the ionic liquid is 1-butyl-3-methylimidazole chloride; the mass ratio of the carbon nanotubes to the polymer monomers is 0.3:1.7; the mass ratio of the carbon nanotubes to the ionic liquids is 0.3:1; the mass ratio of the carbon nanotubes to the water is 0.3:4; and the absorbed dose during irradiation with the cobalt source is 50 kGy; Option 2: A cobalt source irradiates a mixture A; wherein the mixture A comprises carbon nanotubes, polymer monomers, ionic liquids and water; wherein the carbon nanotubes are multi-walled carbon nanotubes; the polymer monomers are acrylamide and acrylic acid, and the mass ratio of acrylamide to acrylic acid is 1:0.7; the ionic liquid is 1-butyl-3-methylimidazole chloride; the mass ratio of the carbon nanotubes to the polymer monomers is 0.3:1.7; the mass ratio of the carbon nanotubes to the ionic liquids is 0.3:2; the mass ratio of the carbon nanotubes to the water is 0.3:4; the absorbed dose during the irradiation of the cobalt source is 50 kGy; Option 3: A cobalt source irradiates a mixture A; wherein the mixture A comprises carbon nanotubes, polymer monomers, ionic liquids and water; wherein the carbon nanotubes are multi-walled carbon nanotubes; the polymer monomers are acrylamide and acrylic acid, and the mass ratio of acrylamide to acrylic acid is 1:0.7; the ionic liquid is 1-butyl-3-methylimidazole chloride; the mass ratio of the carbon nanotubes to the polymer monomers is 0.3:1.7; the mass ratio of the carbon nanotubes to the ionic liquids is 0.3:0.5; the mass ratio of the carbon nanotubes to the water is 0.3:4; the absorbed dose during the irradiation of the cobalt source is 50 kGy; Option 4: A cobalt source is used to irradiate a mixture A; wherein the mixture A comprises carbon nanotubes, polymer monomers, ionic liquids and water; wherein the carbon nanotubes are multi-walled carbon nanotubes; the polymer monomers are acrylamide and acrylic acid, and the mass ratio of acrylamide to acrylic acid is 1:0.7; the ionic liquid is 1-butyl-3-methylimidazole chloride; the mass ratio of the carbon nanotubes to the polymer monomers is 0.3:1.7; the mass ratio of the carbon nanotubes to the ionic liquids is 0.3:1; the mass ratio of the carbon nanotubes to the water is 0.3:4; and the absorbed dose during irradiation with the cobalt source is 25 kGy; Option 5: A cobalt source is used to irradiate a mixture A; wherein the mixture A comprises carbon nanotubes, polymer monomers, ionic liquids and water; wherein the carbon nanotubes are multi-walled carbon nanotubes; the polymer monomers are acrylamide and acrylic acid, and the mass ratio of acrylamide to acrylic acid is 1:0.7; the ionic liquid is 1-butyl-3-methylimidazole chloride; the mass ratio of the carbon nanotubes to the polymer monomers is 0.3:1.7; the mass ratio of the carbon nanotubes to the ionic liquids is 0.3:1; the mass ratio of the carbon nanotubes to the water is 0.3:4; and the absorbed dose during irradiation with the cobalt source is 5 kGy; Option 6: A cobalt source is used to irradiate a mixture A; wherein the mixture A comprises carbon nanotubes, polymer monomers, ionic liquids and water; wherein the carbon nanotubes are single-walled carbon nanotubes; the polymer monomers are acrylamide and acrylic acid, and the mass ratio of acrylamide to acrylic acid is 1:0.7; the ionic liquid is 1-butyl-3-methylimidazole chloride; the mass ratio of the carbon nanotubes to the polymer monomers is 0.3:1.7; the mass ratio of the carbon nanotubes to the ionic liquids is 0.3:1; the mass ratio of the carbon nanotubes to the water is 0.3:4; and the absorbed dose during irradiation with the cobalt source is 50 kGy; Option 7: A cobalt source is used to irradiate mixture B to obtain mixture C; wherein mixture B comprises carbon nanotubes, ionic liquids and water; wherein the carbon nanotubes are single-walled carbon nanotubes; the ionic liquids are 1-butyl-3-methylimidazolium chloride; the mass ratio of the carbon nanotubes, the ionic liquids and the water is 1:1:2000; and the absorbed dose of the cobalt source when irradiating mixture B is 50 kGy; Then, a cobalt source is used to irradiate the mixture D; wherein the mixture D comprises the mixture C, a polymer monomer and water; the polymer monomer is acrylic acid; the mass ratio of the mixture C, the polymer monomer and the water is (1.5:10:90); the absorbed dose when the cobalt source irradiates the mixture D is 50 kGy; Option 8: A cobalt source is used to irradiate mixture B to obtain mixture C; wherein mixture B comprises carbon nanotubes, ionic liquids and water; wherein the carbon nanotubes are single-walled carbon nanotubes; the ionic liquids are 1-butyl-3-methylimidazolium chloride; the mass ratio of the carbon nanotubes, the ionic liquids and the water is 1:2:2000; and the absorbed dose of the cobalt source when irradiating mixture B is 50 kGy; Then, a cobalt source is used to irradiate the mixture D; wherein the mixture D comprises the mixture C, a polymer monomer and water; the polymer monomer is acrylic acid; the mass ratio of the mixture C, the polymer monomer and the water is (2:10:90); the absorbed dose when the cobalt source irradiates the mixture D is 50 kGy; Option Nine: A cobalt source is used to irradiate mixture B to obtain mixture C; wherein mixture B comprises carbon nanotubes, ionic liquids and water; wherein the carbon nanotubes are single-walled carbon nanotubes; the ionic liquids are 1-butyl-3-methylimidazolium chloride; the mass ratio of the carbon nanotubes, the ionic liquids and the water is 1:3:2000; and the absorbed dose of the cobalt source when irradiating mixture B is 50 kGy; Then, a cobalt source is used to irradiate the mixture D; wherein the mixture D comprises the mixture C, a polymer monomer and water; the polymer monomer is acrylic acid; the mass ratio of the mixture C, the polymer monomer and the water is (2.5:10:90); the absorbed dose when the cobalt source irradiates the mixture D is 50 kGy; Option 10: A cobalt source is used to irradiate mixture B to obtain mixture C; wherein mixture B comprises carbon nanotubes, ionic liquids and water; wherein the carbon nanotubes are single-walled carbon nanotubes; the ionic liquids are 1-butyl-3-methylimidazolium chloride; the mass ratio of the carbon nanotubes, the ionic liquids and the water is 1:4:2000; and the absorbed dose of the cobalt source when irradiating mixture B is 50 kGy; Then, a cobalt source is used to irradiate the mixture D; wherein the mixture D comprises the mixture C, a polymer monomer and water; the polymer monomer is acrylic acid; the mass ratio of the mixture C, the polymer monomer and the water is (3:10:90); the absorbed dose when the cobalt source irradiates the mixture D is 50 kGy; Plan 11: A cobalt source is used to irradiate mixture B to obtain mixture C; wherein mixture B comprises carbon nanotubes, ionic liquids and water; wherein the carbon nanotubes are single-walled carbon nanotubes; the ionic liquids are 1-butyl-3-methylimidazolium chloride; the mass ratio of the carbon nanotubes, the ionic liquids and the water is 1:5:2000; and the absorbed dose when the cobalt source is used to irradiate mixture B is 50 kGy; Then, a cobalt source is used to irradiate the mixture D; wherein the mixture D comprises the mixture C, a polymer monomer and water; the polymer monomer is acrylic acid; the mass ratio of the mixture C, the polymer monomer and the water is (3.5:10:90); the absorbed dose when the cobalt source irradiates the mixture D is 50 kGy; Plan 12: The mixture A is polymerized by a crosslinking agent and an initiator to obtain a carbon nanotube gel; wherein the mixture A includes carbon nanotubes, polymer monomers, ionic liquids and water; wherein the carbon nanotubes are multi-walled carbon nanotubes; the polymer monomers are acrylamide and acrylic acid; the crosslinking agent is N,N'-methylenebisacrylamide; the initiator is potassium persulfate, and the mass ratio of acrylamide to the acrylic acid is 1:0.7; the ionic liquid is 1-butyl-3-methylimidazole chloride; the mass ratio of the carbon nanotubes to the polymer monomers is 0.3:1.7; the mass ratio of the carbon nanotubes to the ionic liquids is 0.3:1; the mass ratio of the carbon nanotubes to the water is 0.3:4; the mass ratio of the crosslinking agent to the total mass of the mixture A, the crosslinking agent and the initiator is 0.1:7.2; the mass ratio of the initiator to the total mass of the mixture A, the crosslinking agent and the initiator is 0.1:7.
2.
7. A carbon nanotube gel, characterized in that: The carbon nanotube gel is prepared by the method for preparing the carbon nanotube gel according to any one of claims 3 to 6.
8. A gel electrolyte, characterized in that: The carbon nanotube gel is obtained by subjecting the carbon nanotube gel according to any one of claims 1 to 2 and claim 7 to adsorption-swelling equilibrium with an aqueous solution of an alkali.
9. The gel electrolyte according to claim 8, characterized in that It meets one or more of the following conditions: (1) The alkali is selected from one or more of potassium hydroxide, calcium hydroxide and sodium hydroxide; (2) The mass percentage of the alkali in the aqueous solution of the alkali is 5%-60%, for example, 30%; (3) The gel electrolyte is obtained by allowing the carbon nanotube gel to stand in the alkaline aqueous solution for 1-5 hours and then removing surface moisture.
10. Use of the carbon nanotube gel according to any one of claims 1 to 2 and claim 7 as a gel material in the preparation of gel electrolyte and / or seawater desalination.